Sex-based differences in lymphocyte proliferation in the spleen after vanadium inhalation. (3rd July 2016) - Rodriguez-Lara, Vianey; Muñiz-Rivera Cambas, Angelica; González Villalva, Adriana; Fortoul, Teresa I.
Abstract: Vanadium (V) is a transition metal often adhered to particulate matter and released into the atmosphere as vanadium pentoxide (V2 O5 ) by the burning of fossil fuels. This air pollutant causes adverse effects in the immune system. Lymphocytosis and splenomegaly have been reported with increased white pulp in mice after V inhalation. The effect of V on the immune system as related to sex has been poorly investigated. This study sought to determine if V inhalation (a) produced lymphoproliferation that could explain the changes previously observed in the spleen and in peripheral blood lymphocyte counts and (b) whether any observed effects differed due to gender. Immunohistochemical analyses of Ki-67, a specific proliferation marker, was made in the spleens of CD-1 male and female mice exposed for 1 h, twice a week, over a 12-week period to V2 O5 (at 1.4 mg V2 O5 /m 3 ) by whole-body inhalation; similar analyses were performed on spleens of control mice exposed to vehicle (filtered air). The results showed that in male mice there was a significant increase in percentage of Ki-67 immunopositive lymphocytes starting from the second week and until the end of the exposure. The Ki-67 signal was cytoplasmic and nuclear in the exposed males, while in controls the signal was only nuclear. In female mice, V inhalation singificantly increased the percentage of proliferating lymphocytes only after 1 week of exposure. Ki-67 signal was observed only in the nucleus of lymphocytes from the control and exposed females. The results here help to explain the splenomegaly and lymphocytosis observed previously in male mice and support the lymphoproliferative effect induced by V. Lastly, the finding that there was a sex difference in the effect of vanadium on lymphocyte proliferation suggests a role for sex hormones in potential protection against V immunotoxicity; however, further studies are needed to support this hypothesis.